Cultural, religious and social boundaries between two ethnic communities and the idea of independence for Kosovo and Metohija - Rusche, Renata (Balcanica Posnaniensia. Acta et studia, 2009)
The article addresses the issue of cultural, religious and social boundaries between the two main ethnic communities in Kosovo and Metohija – Albanians and Serbs – in the context of the idea of independence for this region. The aim of the study is to show how different religious traditions, cultural models and historical experiences have shaped the national identity of the two communities, influencing the dynamics of the conflict surrounding the idea of Kosovo's independence. The author asks whether religious and cultural boundaries are an insurmountable obstacle or whether they can become the foundation for understanding. The study is based on the literature on the subject – political science and historical works. The research method is based on comparative interpretation – a comparison of historical and cultural narratives identified with the ethnic groups described. The conclusions indicate that due to the different bases of community identification (for Kosovar Albanians, these are language and the idea of Albanianness, for Serbs, Orthodox Christianity and the Kosovar myth), Kosovo's multiculturalism appears more as a barrier than a bridge. The author points out that the nation-building processes and political aspirations of both communities are part of the broader context of Balkan tensions between tradition and European integration.